Exploring the Diversity of Opinions in Contemporary Islamic Family Law: The Response of Islamic Civil Society Organizations in Banyumas to Changes in the Marriage Age Limit - Iqrar Abdul Halim; M. Wildan Fauzbika; Muchammad Abdur Rochman (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Purpose - One of the consequences of the enactment of Law Number 16 of 2019 amending Law Number 1 of 1974 is the increase in applications for marriage dispensations, particularly in the Banyumas region. With this issue, the response of Islamic organizations is something that must be accommodated, because these organizations are currently the institutions that oversee and provide solutions to contemporary issues in the field of Islamic family law. Based on this premise, the research problem formulated is how Islamic organizations in Banyumas respond to the changes in the marriage age limits under Law Number 1 of 1974 amended by Law Number 16 of 2019 concerning Marriage Age Limits. Design/methods/approach - This study adopts a field research approach, where the primary method involves conducting interviews with several Islamic organizations in Banyumas, including Al Irsyad Al Islamiyah, Indonesian Islamic Da'wah Institute (Lembaga Dakwah Islam Indonesia/LDII), Muhammadiyah, and Nahdlatul Ulama. The object of this research is the response of Islamic organizations in Banyumas. Data collection is carried out using interview, observation, and documentation methods. The data gathered by the author is primarily sourced from interviews with these Islamic organizations in Banyumas. Findings - The findings of this study reveal that Islamic civil organizations in Banyumas express that the changes in marriage age limits pose no issues and are in agreement with the amendments. They argue that Islam does not impose absolute restrictions regarding marriage age, and the matter remains debatable among scholars (Ulama) within the realm of ijtihad (independent legal reasoning). Furthermore, they assert that determining these limits does not violate Islamic law, considering that maturity for marriage is also a factor, with the goal of achieving a harmonious family (Sakinah, Mawaddah, and Warrahmah) and raising future generations to be virtuous. This is in accordance with the principle of maqashid sharia as a paradigm of contemporary Islamic family law. Research implications/limitations - This research is limited to a field study whose object is Islamic civil organizations in Banyumas, including Muhammadiyah, Nahdlatul Ulama, LDII, and Al Irsyad Al Islamiyyah. Originality/value - This research is expected to contribute theoretically and practically to the development of legal construction regarding the age limit of marriage in Indonesia.